The impact of public policy of family doctor contracting on medical expenses from the perspective of residents at community level in China - Li, Lele; He, Xiaotong; Zhang, Caihua (Frontiers in Psychology, 2023)
objective: To analyze the impact of the contract of family doctors in community-level in Beijing on residents' medical expenses, so as to explore the efficacy of family physician contract service to facilitate the hierarchical treatment system. This study pioneeringly used the panel data of medical records and medical insurance settlement details provided by a community hospital in Beijing. By analyzing the correlation between family doctors and medical expenses, the study provided empirical support for the advancement of family doctor contracting in China. Methods: Using the panel data of medical records and medical insurance settlement details of 5851 residents in a community hospital in Beijing from January 2018 to May 2021 for a total of 41 months, mixed-effects model and random-effects model were used for analysis. Results: The contract of family doctor has significantly increased residents' medical expenses. The types of medical insurance and whether patients with chronic diseases have a significant impact on residents' medical expenses. Conclusion: Family doctor contracting increases the probability of residents seeing a doctor in community hospitals. Community family doctor contracting services should be vigorously promoted, especially for special groups such as chronic disease patients and the elderly. The increase in the contracting rate of family doctors will become an important starting point for promoting hierarchical medical system and increasing the primary treatment at the community-level.